Pekerti Training to Improve Lecturers’ Instructional Quality as Professional Academics - Agus Prasetya; Stefani Stefani (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2019)
Social phenomena in the higher education environment currently sees competition for academic staffs to obtain functional positions in order to obtain social status and recognition as lecturers. Academic staffs are required to have the following competencies namely pedagogical, academic, social, personal, professional and to improve their competencies by participating in trainings such as Aplied Approach (AA) training. By participating in AA training, an academic staff is required to understand what must be possessed as a lecturer especially in making Lecture Even Unit or Tutorial Program Design and Tutorial Event Unit. The objective is to carry out technical training so that the lecturer understands instructional basic techniques such as teaching methodologies, understanding teaching and learning techniques, teaching evaluation, understanding and being able to make the Tutorial Program Design and Tutorial plan, so that they become professional academic personnel. namely affective social actions, specific social actions, social actions on the basis of values ​​and traditional social actions. The expected final results with AA-type training, the ability of lecturers to manage teaching learning process is more quality so that professional academics are created, besides being one of the certification requirements.